Concentration of elements in the hair of growing and adult dogs. Issue 1 (2nd January 2019) - Sgorlon, Sandy; Mattiello, Alessandro; Ronutti, Linda; Sandri, Misa; Stefanon, Bruno
Abstract: The aim of the study was to investigate element concentrations in the hair of growing and adult dogs. Overall, 39 dogs were recruited in a kennel, split in 4 groups: G1, 10 puppies of small size breeds; G2, 6 puppies of medium size breed; G3, 11 adult dogs of medium size breeds; G4, 12 adult dogs of toy breeds. The dogs of each group were fed 4 different complete diets, according to the requirements. Hairs were sampled at the beginning of the study (D0) and after 60 days (D60). Elements were analysed in triplicate using ICP-OES. In the hair of the adult dogs of the G3 group the concentration of Al ( p  < .01) was lower and in the G2 group the concentration of Zn was higher ( p  < .01) than in the other groups. Cu and Mn concentrations in the hair were higher ( p  < .01 and p  < .05, respectively) in puppies fed G1 and G2 diets in comparison to adult dogs fed G3 and G43 diets. Hair concentrations of K, Li and Na were higher at D60 in comparison with D0 ( p  < .01). Correlations between concentrations in the hair of Al and Fe, Al and Mg and Fe and Mg were highly significant ( p  < .01). Present data do not support the use of element concentrations in the hair to assess their nutritional supply but, likely, they can be used in relation to physiological status of the animals. Further studies are required to investigate the factors affecting element concentrations in the hair of dogs. Highlights: Concentrations of Cu, Mn and Zn in the hair differed between growing and adult dogs; Al concentration in hair was highly correlated with Fe and Mg; Several factors other than nutritional supply regulate element deposition in the hair